A site-specific, sustained-release drug delivery system for aneurysmal subarachnoid hemorrhage - Hänggi, Daniel; Etminan, Nima (Neurotherapeutics, 2016)
Nimodipine is the only drug approved for use by the Food and Drug Administration for improving outcome after aneurysmal subarachnoid hemorrhage (SAH). It has less than optimal efficacy, causes dose-limiting hypotension in a substantial proportion of patients, and is administered enterally 6 times daily. We describe development of site-specific, sustained-release nimodipine microparticles that can be delivered once directly into the subarachnoid space or cerebral ventricles for potential improvement in outcome of patients with aneurysmal SAH. Eight injectable microparticle formulations of nimodipine in poly(DL-lactide-co-glycolide) (PLGA) polymers of varying composition were tested in vitro, and 1 was advanced into preclinical studies and clinical application. Intracisternal or intraventricular injection of nimodipine-PLGA microparticles in rats and beagles demonstrated dose-dependent, sustained concentrations of nimodipine in plasma and cerebrospinal fluid for up to 29 days with minimal toxicity in the brain or systemic tissues at doses <2 mg in rats and 51 mg in beagles, which would be equivalent of up to 612-1200 mg in humans, based on scaling relative to cerebrospinal fluid volumes. Efficacy was tested in the double-hemorrhage dog model of SAH. Nimodipine-PLGA microparticles significantly attenuated angiographic vasospasm. This therapeutic approach shows promise for improving outcome after SAH and may have broader applicability for similar diseases that are confined to body cavities or spaces, are self-limited, and lack effective treatments.
Gesehen am 04.04.2019